PEMBERDAYAAN GURU DALAM PENGGUNAAN PLATFORM GOOGLE CLASSROOM PADA MASA NEW NORMAL DI MTSS NURUL QUR’AN: PEMBERDAYAAN GURU DALAM PENGGUNAAN PLATFORM GOOGLE CLASSROOM PADA MASA NEW NORMAL DI MTSS NURUL QUR’AN - Silvi Listia Dewi; Rahmi Hayati; Misnawati Misnawati; Zuraini Zuraini; Misnar Misnar (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Education is the spearhead in achieving the progress and success of a nation and a State. The state must have a generation that is ready to manifest it. The Educators or teachers are the main keys in creating a discerning nation. There are extraordinary challenges that must be faced by the educators or teachers during the Covid 19 pandemic. However, this is not an obstacle in creating and producing Indonesia's golden generation. Online learning is a solution offered by the Government of Indonesia, where students learn from home and teachers work from home. In this new normal era, teachers are required to teach online. A variety of media platforms can be utilised in this situation, such as Google Classroom Platform; is one of the media that is very suitable for teachers to apply in the teaching and learning process. Through Google Classroom, teachers can provide material, learning videos, and modules, manage student assignments, exams, and check attendance. The advantage of learning online does not make students tired like offline activities, fun, and it can provide new experiences for them.